COMPLICATION OF MANDIBULAR ANGLE FRACTURE INVOLVING LOWER THIRD MOLAR IMPACTION: CASE REPORT - Savira Nurazky Yuniar; Yayun Siti Rochmah (Indonesian Journal of Dentistry, 2025)
Introduction : Mandibular angle fractures frequently result from trauma and are often complicated by the presence of impacted third molars, which can increase the risk of infection. Case(s) : This case report presents 2 cases of mandibular angle fractures involving the third molar. In the first case, the tooth was not extracted during the previous surgery, and an infection occurred during 6 months post-ORIF. The second case, ORIF was performed along with the extraction of the third molar followed by inter-maxillary fixation, resulting in satisfactory outcomes. Conclusion: Tooth involved in fractures line can increase infection risk. Extraction of impacted third molars within the fracture line can help reduce infection risk and promote healing.